Prevalence and Associated Factors of Diabetic Foot at Risk among Type 2 Diabetes Mellitus Patients Attending Primary Health Clinics in Kuantan - Azmi, NH; Abdul Hadi, A; Md Aris, MA; Nasreen, HE; Che-Ahmad, A (IIUM Medical Journal Malaysia, 2020)
Introduction: The diabetic foot at risk is the diabetic foot which is at risk of ulceration, hence the importance of identifying the foot at this stage. This study aims to assess the prevalence of diabetic foot at risk and its associated factors among type 2 diabetes mellitus patients’ attending primary health clinics in Kuantan. Methods and methods : This was a cross-sectional study conducted at four primary health clinics in Kuantan involving 450 study participants who were selected by using universal sampling method. Foot examination was carried out and foot at risk was classified based on the Kings’ Classification. Multiple logistic regressions were performed to identify the predictors for diabetic foot at risk. Results: The prevalence of diabetic foot at risk was 31.3%. Multivariate logistic regression analysis identified age (OR 1.04, 95% CI: 1.01-1.06), smoker (OR 4.11, 95% CI: 1.96-8.63) and duration of diabetes more than 10 years (OR1.77, 95% CI: 1.05-2.98) as risk factors for diabetic foot at risk. Respondents with higher diabetic foot practice score (OR 0.87, 95% CI: 0.77-0.98) have lesser risk of developing diabetic foot at risk. Conclusion: Patients who are older, smoker and/or have chronic diabetes are predicted to be at higher risk to develop the diabetic foot at risk. This study also showed that patients with better foot care practice has lesser risk. Therefore, these are the groups of patients that need to be targeted for early detection and intervention to prevent serious complications.